Dari Pembungkaman ke Perlawanan: Transformasi Agensi Perempuan dalam A Thousand Splendid Suns melalui Perspektif Muted Group Theory - Indra, Daswandi Budi (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2025)
This study analyzes the transformation of female agency in Khaled Hosseini’s novel A Thousand Splendid Suns through the lens of Muted Group Theory (MGT). Employing a qualitative text-based approach, the analysis explores how the character Mariam undergoes a process of silencing shaped by patriarchal social structures and male-dominated language, and how she gradually reconstructs her voice through acts of resistance. The findings reveal that silencing of women occurs not only physically and verbally but also symbolically and epistemically. However, personal resistance, women’s solidarity, and self-awareness emerge as key elements in articulating female agency. Through Mariam’s narrative, the study demonstrates that women are capable of creating alternative spaces of meaning beyond dominant systems. Accordingly, this research not only extends the application of MGT in literary contexts but also underscores literature as an emancipatory arena reflecting women’s struggles against social injustice. Furthermore, it highlights the potential of enriching MGT through dialogue with intersectionality, while offering practical implications for gender-sensitive communication education and media literacy.